What is the Gaming Lifestyle? : An exploratory investigation. - Matheus JosÃ© Machado Dutra (Bina Nusantara University, 2021)
This research explored the topic of lifestyle in the ambit of gaming. A total of 711 valid respondents from 67 countries took part in a questionnaire designed to gather information about the Gaming Lifestyle (GLS). The objective was to identify what game-related practices, habits, attitudes, and beliefs characterized this way of living. The exploratory factor analysis was employed to uncover underlying factors that could answer this question. Results pointed that Six Factors influence the GLS: competition, media, microtransactions, marketing and communication, socialization, and enjoyment. This paper contributes to the field of game studies by deepening our understanding of how gamers are impacted by in-game and out-game daily experiences.